Early rehabilitation for the prevention of postintensive care syndrome in critically ill patients: a study protocol for a systematic review and meta-analysis. Issue 3 (1st March 2017) - Kondo, Yutaka; Fuke, Ryota; Hifumi, Toru; Hatakeyama, Junji; Takei, Tetsuhiro; Yamakawa, Kazuma; Inoue, Shigeaki; Nishida, Osamu
Abstract : Introduction: Postintensive care syndrome (PICS) is defined as a new or worsening impairment in cognition, mental health and physical function after critical illness. There is little evidence regarding treatment of patients with PICS; new directions for effective treatment strategies are urgently needed. Early physiotherapy may prevent or reverse some physical impairments in patients with PICS, but no systematic reviews have investigated the effectiveness of early rehabilitation on PICS-related outcomes. The purpose of this systematic review is to evaluate whether early rehabilitative interventions in critically ill patients can prevent PICS and decrease mortality. Methods: We will conduct a systematic review and meta-analysis of early rehabilitation for the prevention of PICS in critically ill adults. We will search PubMed, EMBASE and the Cochrane Central Register of Controlled Trials for published randomised controlled trials. We will screen search results and assess study selection, data extraction and risk of bias in duplicate, resolving disagreements by consensus. We will pool data from clinically homogeneous studies using a random-effects meta-analysis; assess heterogeneity of effects using the χ 2 test of homogeneity; and quantify any observed heterogeneity using the I 2 statistic. We will use the Grading of Recommendations Assessment, Development and Evaluation approach to rate the quality of evidence. Discussion: This systematic review will present evidence on the prevention of PICS in critically ill patients with early rehabilitation. Ethics: Ethics approval is not required. Dissemination: The results will be disseminated via peer-reviewed journal publication, conference presentation(s) and publications for patient information. Trial registration number: CRD42016039759.